Hartmann’s Procedure Versus Intersphincteric Abdominoperineal Excision in Patients with Rectal Cancer: Report from the Swedish Colorectal Cancer Registry (SCRCR) - Viktor Åkerlund, MD; Maziar Nikberg, MD, PhD; Philippe Wagner, PhD; Abbas Chabok, MD, PhD (Annals of Surgery Open)
Objective:. The primary outcome was to compare overall postoperative surgical complications within 30 days after Hartmann’s procedure (HP) compared with intersphincteric abdominoperineal excision (iAPE). The secondary outcome was major surgical complications (Clavien-Dindo ≥ III). Background:. There is uncertainty regarding the optimal surgical method in patients with rectal cancer when an anastomosis is unsuitable. Methods:. Rectal cancer patients with a tumor height >5 cm, registered in the Swedish Colorectal Cancer Registry who received HP or iAPE electively in 2017–2020 were included, (HP, n = 696; iAPE, n = 314). Logistic regression analysis adjusting for body mass index, American Society of Anesthesiologists classification, sex, age, preoperative radiotherapy, tumor height, cancer stage, operating hospital, and type of operation was performed. Results:. Patients in the HP group were older and had higher American Society of Anesthesiologists scores. The mean operating time was less for HP (290 vs 377 min). Intraoperative bowel perforations were less frequent in the HP group, 3.6% versus 10.2%. Overall surgical complication rates were 20.3% after HP and 15.9% after iAPE (P = 0.118). Major surgical complications were 7.5% after HP and 5.7% and after iAPE (P = 0.351). Multiple regression analysis indicated a higher risk of overall surgical complications after HP (odds ratio: 1.63; 95% confidence interval = 1.09–2.45). Conclusions:. HP was associated with a higher risk of surgical complications compared with iAPE. In patients unfit for anastomosis, iAPE may be preferable. However, the lack of statistical power regarding major surgical complications, prolonged operating time, increased risk of bowel perforation, and lack of long-term outcomes, raises uncertainty regarding recommending intersphincteric abdominoperineal excision as the preferred surgical approach.